Wolves of the Calla - King, Stephen, 1947- (King, Stephen, 1947- Dark tower, 2003)
Wolves of the Calla continues the adventures of Roland, the Last Gunslinger and survivor of a civilized world that has "moved on." Roland's quest is ka, an inevitable destiny -- to reach and perhaps save the Dark Tower, which stands at the center of everywhere and everywhen. This pursuit brings Roland, with the three others who've joined his quest to Calla Bryn Sturgis, a town in the shadow of Thunderclap, beyond which lies the Dark Tower. Before advancing, however, they must face the evil wolves of Thunderclap, who threaten to destroy the Calla by abducting its young.